Manufacturing resources planning II: A study of failure factors and guidelines for initial software acquisition, selection and implement process - Kang, Eng Thye; Jamaludin, Roslan (Pusat Penyelidikan dan Perundingan, Universiti Utara Malaysia, 2000)
Almost two decades MRP II has been a popular tool in supporting the manufacturing industries worldwide. Many organizations seeking, this application to be more competitive by effective used of computerized information system. However, feedbacks from industries on the implementation of MRP II are not favorable. Based on the statistics by independent body, 80% of WRP II implementation are reported as failure besides its good points. Various reasons are given regarding the failure of MRP II implementation. The main purpose of this study is to investigate the factors that contribute to the MRP II failures and to assist especially Malaysian companies with an appropriate guidelines before purchasing and implementing any MRP II packages.